Sustainable Empowerment Strategies in Rural Areas: A Qualitative Study on Women Farmer Groups - Yudan Hermawan; Fitta Ummaya Santi; Riko Septiantoko; Rita Bekti Utami (Journal of Nonformal Education, 2025)
Background: Community empowerment plays an important role in driving sustainable development, especially in rural areas. The Bejiharjo Farmer Women Group (KWT) is an example of community-based empowerment initiatives that have succeeded in developing social entrepreneurship. Through women's active participation, capacity building, and utilization of local resources, this KWT has been able to generate significant economic and social impacts for its communities. Research Urgency: It is important to understand the empowerment pattern that KWT Bejiharjo applies in building sustainable social enterprises, in order to replicate similar models in other villages. Identification of key success factors can make a major contribution to the development of local potential-based women's and community empowerment programs. Research Objectives: This study aims to explore the patterns of community empowerment implemented by the Bejiharjo Women Farmers Group (KWT) and identify the key elements that drive the success and sustainability of community-based social entrepreneurship. Research Method: A qualitative case study approach was employed, involving in-depth interviews, participatory observation, documentation, and focus group discussions. Thematic and narrative analyses were conducted to identify key empowerment patterns, with data triangulation ensuring validity and reliability. Research Findings: The results of the study show that the empowerment carried out by KWT Bejiharjo has succeeded in increasing members' ownership and sense of responsibility for group activities, along with the growth of collective commitment and social bonds. In addition, intensive training from various partners also improves members' skills and knowledge in the fields of production, marketing, and business management. This effort is supported by the utilization and diversification of local resources, which not only strengthens the household economy, but also creates added value through processed products and expands the potential of educational agrotourism in the local area. Research Conclusion: The empowerment model applied by KWT Bejiharjo has succeeded in creating a sustainable social entrepreneurship ecosystem. Shared ownership, capacity building, and utilization of local potential are the main foundations in building economic and social independence at the community level Research Novelty/ Contibution: This research contributes to the development of a community-based empowerment model that is oriented towards social entrepreneurship. The findings in this study can serve as a reference for the development of sustainable empowerment strategies in other rural communities with a participatory and local potential-based approach.